2020
DOI: 10.1042/bcj20190188
|View full text |Cite
|
Sign up to set email alerts
|

Handing off iron to the next generation: how does it get into seeds and what for?

Abstract: To ensure the success of the new generation in annual species, the mother plant transfers a large proportion of the nutrients it has accumulated during its vegetative life to the next generation through its seeds. Iron (Fe) is required in large amounts to provide the energy and redox power to sustain seedling growth. However, free Fe is highly toxic as it leads to the generation of reactive oxygen species. Fe must, therefore, be tightly bound to chelating molecules to allow seed survival for long periods of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 123 publications
(177 reference statements)
0
17
0
Order By: Relevance
“…S11. It is currently unclear how iron is transported through the plant cytosol, although NA is thought to play a key role (Mari et al ., 2020). Our study suggests that vesicle transport could also be involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S11. It is currently unclear how iron is transported through the plant cytosol, although NA is thought to play a key role (Mari et al ., 2020). Our study suggests that vesicle transport could also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular pathways of iron and zinc uptake from the soil into plant roots are relatively well understood, but we know little about mineral loading into the seeds and subsequent distribution to different tissues (Mari et al ., 2020). Recent isotope labelling studies in Arabidopsis suggested that virtually all the iron in seeds was remobilized from senescing leaves (and other organs) with only an indirect contribution from uptake by the roots (Pottier et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig S11. It is currently unclear how iron is transported through the plant cytosol, although NA is thought to play a key role (Mari et al, 2020). Our study suggests that vesicle transport could also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…5). NA is known to be important for iron loading into the grain (Mari et al, 2020). Interestingly, two different NAS genes were upregulated in aleurone and starchy endosperm, TaNAS9 and TaNAS6 , respectively.…”
Section: Discussionmentioning
confidence: 99%